EFEKTIFITAS TERAPI SHALAT BAHAGIA UNTUK MENGURANGI PROBLEM YANG TIDAK KUNJUNG SELESAI (UNFINISHED BUSINESS) DI SURABAYA (Jurnal Bimbingan dan Konseling Islam, 2013)
The problems examined in this study ie Is Happy Prayer Therapy Effective in Reducing Problem The Not Visit Finish ( Unfinished Business ) in Surabaya . This study aims to determine the effectiveness Prayer Happy Therapy in Reducing Problem The Not Visit Finish ( Unfinished Business ) in Surabaya . This study uses quantitative methods are useful to explore the facts and data. The subjects in this study are the ones who follow Joy Prayer Therapy Training ( PTSB ) in Central Siwalankerto institutions YAQUTA No. KUN . 66 . Data collection used is the observation , interviews , documentation and delivery using a questionnaire with a Likert scale models of computation techniques via the t-test ( Paired - Sample T - Test ) . Results of t-test ( Paired - Sample - T - Test ) between before treatment and after prayers Happy Happy Prayer Therapy , shows that t is greater than t table ( 10 699 > 1,662 ) with an average ( mean ) after doing therapy Happy prayer of 69.9674 is greater than before the Blessed prayer Therapy of 61.0217 means Therapy Effective prayer Happy to Handle Unfinished Business.Keywords : Happy Prayer Therapy , Unfinished Business .